Hispanic arts committee gets grant from US West (Raton, New Mexico Raton Range, 1991)
Article about a grant received from the US west to the Hispanic Arts Committee and what it was used for.
Newspaper article + Photograph of Augustine Vega and Joe Apache
Master list item #: 3
File location is in the Raton file Cabinet
Keywords: Apache, Joe -- Public relations coordinator for US West; Vega, Augustine -- Chairman to the Hispanic Arts Committee; Radford, Ronald -- Flamenco guitar viruoso; US West, Inc; Art Grants; Hispanic Arts; Flamenco Guitar Virtuoso; Local Businesses; Arts and Humanities Council; Raton, New Mexico